2014
DOI: 10.1155/2014/923290
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Error in Substance Use Prevalence Surveys

Abstract: Population-based estimates of substance use patterns have been regularly reported now for several decades. Concerns with the quality of the survey methodologies employed to produce those estimates date back almost as far. Those concerns have led to a considerable body of research specifically focused on understanding the nature and consequences of survey-based errors in substance use epidemiology. This paper reviews and summarizes that empirical research by organizing it within a total survey error model frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
130
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(138 citation statements)
references
References 230 publications
(229 reference statements)
4
130
0
4
Order By: Relevance
“…Our final models, which include statistical adjustment for demographic and socioeconomic characteristics as well as substance use prior to age 18, found no associations between the policy and substance use; the estimated odds ratios were tightly clustered around 1 and none reached statistical significance. These findings confirm and extend those of a prior study using data from the BRFSS, by examining additional outcomes and using more robust data on substance use outcomes; in contrast to the BRFSS, the NSDUH uses in-home computer assisted interview methods rather than telephone interviews resulting in higher and likely more accurate prevalence estimates (Johnson, 2014; Miller et al, 2004). Contrary to the theory of ex ante moral hazard, risky substance use does not appear to be responsive to health insurance coverage in this age group.…”
Section: Discussionsupporting
confidence: 80%
“…Our final models, which include statistical adjustment for demographic and socioeconomic characteristics as well as substance use prior to age 18, found no associations between the policy and substance use; the estimated odds ratios were tightly clustered around 1 and none reached statistical significance. These findings confirm and extend those of a prior study using data from the BRFSS, by examining additional outcomes and using more robust data on substance use outcomes; in contrast to the BRFSS, the NSDUH uses in-home computer assisted interview methods rather than telephone interviews resulting in higher and likely more accurate prevalence estimates (Johnson, 2014; Miller et al, 2004). Contrary to the theory of ex ante moral hazard, risky substance use does not appear to be responsive to health insurance coverage in this age group.…”
Section: Discussionsupporting
confidence: 80%
“…Because of how survey items were nested (e.g., someone who reported use in the past 30 days would have also reported use in the past 6 months), sensitivities across recall periods for a substance should have been equal. Instead, the monotonic increase with longer recall period, as observed in other studies [5, 46, 47], suggests participants may be more willing to disclose substance use if there is perceived distance from the behavior, possibly due to impression management [2, 3, 48]. Alternatively, there may be temporal recall errors, such as a telescoping effect [48].…”
Section: Discussionmentioning
confidence: 84%
“…Framed differently, self-reported substance use data appeared as valid at baseline as they were after multiple waves of follow-up and multiple years of research participation, respectively, though a marginal finding toward greater disclosure of non-marijuana drug use among those recruited in 2015 may hint at possible generational differences. Survey methodologists have long been concerned about threats to construct validity due to the research process itself, such as altered behavior in response to self-evaluation, reduced social desirability bias due to familiarity with the researchers and no observed consequences from reporting illegal or stigmatized behaviors, and practice effects [2, 3, 48, 60]. Our study, however, demonstrated that impression management, the main component of social desirability bias, was sustained despite participants’ becoming more comfortable with study procedures and staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations